A Brief Historic Review of Special Education for Students with Extensive Support Needs in the US, Hawai’i, and Japan - Matthews, Somer (Global Journal of Educational Studies, 2024)
The purpose of this paper is to provide a scoping review situating the history of special education for students with extensive support needs (ESN) in the United States and Hawaii, as well as in Japan and other parts of East Asia. With the continued globalization of our interactive world, none of our educational systems exist in a vacuum; our systems have and will continue to influence one-another. This influence is evident throughout the literature, showing that though the timing of special education reform in each of these regions differ, many parts of our educational systems mirror one another. Despite our differences, what we all share is a common goal of reducing the stigmatization of students with disabilities in our schools and societies, and we will only achieve that through a global shift toward presumed competence.